Effect of the combination of a cold-water temperature and exogenous estrogens on feminization, growth, gonadosomatic index and fat muscle content of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) - Lazaro-Velasco, Angel [UNESP]; Isidro-Cristobal, Helsi M. [UNESP]; Pablo Alcantar-Vazquez, Juan; Antonio-Estrada, Carolina; Calzada-Ruiz, Daniel; Moreno-de La Torre, Raul (Univ Catolica De Valparaiso, 2019)
The use of water temperature to modify sex proportion in Nile tilapia has been suggested as an alternative to eliminating the use of steroids since it was discovered that it has an important role in the sex differentiation process. However, the use of cold-water temperatures to achieve feminization has rarely been explored and never has it been combined with exogenous estrogens. This work aimed to determine if the proportion of females could be increased by combining low concentrations of estrogens with a cold-water temperature, and describing its effect on growth parameters, gonadosomatic index, and fat muscle content. Two experiments were carried out, each one set at a specific water temperature (27.5 and 21.5 degrees C). In each experiment four treatments (per triplicate) were evaluated (control-no estrogens-, estradiol-17 beta E2, 17 alpha-ethinylestradiol EE2 and diethylstilbestrol DES). Higher feminization rates were observed in all groups, including the control group, reared at 21.5 degrees C. Growth parameters showed significantly higher values (P < 0.05) for the groups reared at 27.5 degrees C. The control group and the group fed E2 reared at 21.5 degrees C showed significantly higher (P < 0.05) values of gonadosomatic index than that observed in the groups reared at 27.5 degrees C. Fat muscle content was significantly higher (P < 0.05) in both experiments for the groups fed E-2 and EE2. The fry used showed a high tendency towards feminization by exposure to a cold-water temperature. Our results allow us to consider E-2 (21.5 degrees C) the best option for the development of YY technology.
Keywords: Oreochromis niloticus; feminization; thermosensitivity; growth depression; gonads; fat in muscle